Is urinary free cortisol of value in the diagnosis of Cushing's syndrome? - Alexandraki, K; Grossman, AB (2011)
PURPOSE OF REVIEW: Cushing's syndrome results from prolonged and inappropriately high exposure of tissues to glucocorticoids. Biochemical tests are always needed to confirm the clinical suspicion: these include measurement of excess total endogenous cortisol secretion assessed by 24-h urinary free cortisol (UFC), loss of the normal feedback of the hypothalamo-pituitary-adrenal axis assessed by suppressibility after dexamethasone testing, and disturbance of the normal circadian rhythm of cortisol secretion assessed by midnight serum or salivary cortisol. This review focuses on recent data emerging on the value of UFC as a screening test for Cushing's syndrome. RECENT FINDINGS: Considerable evidence has emerged regarding the utility of UFC in the diagnosis of Cushing's syndrome because of its long-term use in clinical practice. Despite the fact that UFC assesses the active (free) component of cortisol, the methodological difficulties in 24-h urine collection and in assay precision have rendered this screening technique increasingly unpopular. Furthermore, the increased prevalence of mild, preclinical or cyclic Cushing's syndrome along with the fact that cortisol is not uniformly secreted during the day do not support its use as a screening test, although strikingly high levels can be useful. SUMMARY: Since the sensitivity and specificity of UFC are less than ideal when compared with other diagnostic modalities, we suggest the use of other more novel tests as first-step diagnostic tests to screen for hypercortisolaemia.